COUNTER TERRORISM IN NIGERIA: AN ASSESSMENT OF BUHARI GOVERNMENT’S RESPONSE TO BOKO HARAM INSURGENCY - Nosiri, Uzoma D.; Ibekwe, Emmanuel O. (African Journal of Social and Behavioural Sciences, 2021)
The Boko Haram insurgency has been regarded as one of the deadliest terrorist groups in the world. Its operations since the year 2009 have contributed to thousands of deaths and displacement of people in Nigeria and other neighbouring countries. Therefore, this work critically assessed the Buhari’s government response towards combating the Boko Haram terrorist activities in Nigeria. The specific objectives are to ascertain the effectiveness of Buhari government’s response to the Boko Haram activities in Nigeria; identify the problems encountered by Buhari’s administration in combating the insurgency in Nigeria and proffer suitable solutions or strategies for effective counter terrorism in Nigeria. This paper adopted Galula’s Counter-insurgency theory as the framework for analysis. Data was sourced through secondary sources and analyzed with both qualitative and quantitative methods. This paper revealed that despite the fact that the Buhari’s government has achieved some degree of success in combating Boko Haram insurgency (in terms of reduction of incidence of attacks and number of causalities; and recapture of territories), the success has not been significant or effective in the fight against the Boko Haram insurgent. This is because the Boko Haram is still carrying out successful operations or attacks. In addition, it revealed that the use of unconventional warfare by the terrorists; issue of globalization; poor border security; Boko Haram’s network with international terrorist groups; corruption etc are the factors that pose challenge to Buhari’s administration towards combating the Boko Haram insurgency. This paper recommended that for the need for effective training of security personnel on counter terrorism and insurgency; adequate use of ICT or modern technologies; effective border security; strengthening of the cooperation and coordination of security agencies; strengthening of Multinational Joint Task Force and solving the problem of corruption etc.